Business knowledge for IT in Islamic finance : a complete handbook for IT professionals. (Bizle professional series., 2009)
"'Business Knowledge for IT in Islamic Finance' deals with the convergence of business and IT in the Islamic finance industry and is designed to provide the platform for IT professionals to exploit the future demand for talent in this industry. The chapters in this book contain information on the fundamentals of Islamic finance, the features that sets the Islamic finance industry apart form the mainstream finance industry, a number of the prohibitions and business ethics in Islamic Finance, overview of business transactions and the legal process underpinning these transactions; major players in the Islamic Finance world; and, major systems from notable vendors used for lending, financing, capital markets transactions and insurance in the Islamic finance space"--Resource description page